THE NEW NORMAL" IN THE CONTEXT OF BUILDING A SOCIETY OF «MODERATE PROSPERITY» IN MODERN CHINA - M. Romanenko; Y. Xu (Вестник университета)
The article deals with the content of the course «new rule» in the context of creation in the China for the year 2021 the company "average prosperity".